Recovery method of thermosetting resin matrix composite frame and application of recovered material
By mixing and reacting the frame of the thermosetting resin-based composite with the degradation solution, it can achieve chemical degradation, solving the problem of being unable to be reused after decommissioning. The recovered fibers and degradation products can be used in a variety of applications, achieving sustainable utilization of resources .
Patent Information
- Application Number
- CN202411721188.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-11
AI Technical Summary
The frames of thermosetting resin-based composite materials cannot be remodeled and used after decommissioning, resulting in environmental pollution and waste of resources, and lack of effective degradation and recycling methods.
By mixing the border of the thermosetting resin-based composite material with the degradation solution at a preset weight ratio and reacting under preset conditions, the thermosetting resin matrix is degraded to obtain a degradation product that can be used for foaming materials, adhesives and coatings.
Chemical degradation of thermosetting resin-based composite frames is achieved, and the recovered fibers can be used for reinforced composite materials. The degradation products can be used in a variety of industrial applications, solving the problems of environmental pollution and resource waste.
Smart Images

Figure CN119410026A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a method for recycling a thermosetting resin-based composite material frame and application of the recycled material. Background Art
[0002] Fiber reinforced polymer (FRP) is a composite material formed by winding, molding or pultrusion of reinforcing fiber materials and matrix materials. Fiber reinforced polymer composites are gradually replacing aluminum alloys and other materials due to their advantages of light weight, excellent mechanical properties and low cost, and are widely used in photovoltaic frames.
[0003] The current composite material frames are mainly thermosetting resin-based composite materials. After cross-linking and curing, thermosetting resins can form a stable three-dimensional network structure, which makes them have good heat resistance, dimensional stability, durability and other advantages. However, this also makes them unable to be reshaped and reused, which is also a pain point for the large-scale application of thermosetting resin-based composite materials. The landfill treatment of retired or scrapped products will seriously pollute the environment and cause excessive waste of resources. How to achieve the degradation and recycling of composite material frames through reasonable methods is an inevitable goal for achieving sustainable development. Summary of the invention
[0004] In order to solve the above technical problems, the present application aims to provide a method for recycling thermosetting resin-based composite material frames, which can achieve degradation and recycling of the thermosetting resin matrix, solving the environmental pollution and recycling problems after the large-scale application of composite materials.
[0005] According to a first aspect of the present application, a thermosetting resin-based composite material frame is provided, wherein the thermosetting resin-based composite material frame comprises a thermosetting resin matrix, and the recycling method comprises:
[0006] Mixing the thermosetting resin-based composite material frame and the degradation liquid according to a preset weight ratio to obtain a mixture;
[0007] allowing the mixture to react under preset conditions to degrade the thermosetting resin matrix;
[0008] Wherein, the thermosetting resin matrix includes ester bonds and / or urethane bonds;
[0009] The preset weight ratio is 1:3.0-50.0.
[0010] In some embodiments of the present application, the preset conditions include: maintaining 0.5-24.0h under the conditions of temperature of 20-300°C, pressure of 0-20MPa, and stirring rate of 0-2000r / min.
[0011] In some embodiments of the present application, the degradation liquid includes one of an acidic degradation liquid, an alkaline degradation liquid, and a metal ion degradation liquid.
[0012] In some embodiments of the present application, when the degradation liquid includes an acidic degradation liquid, the acidic degradation liquid includes an acidic compound, and the acidic compound includes one or more of sulfuric acid, hydrochloric acid, nitric acid, carbonic acid, p-toluenesulfonic acid, acetic acid, phosphotungstic acid, trifluoroacetic acid, and trifluoromethanesulfonic acid;
[0013] When the degradation liquid comprises an alkaline degradation liquid, the alkaline degradation liquid comprises an alkaline compound, and the alkaline compound comprises one or more of potassium hydroxide, sodium hydroxide, sodium bicarbonate, aluminum hydroxide, sodium carbonate, 4-dimethylaminopyridine, alkyl copper lithium, and tert-butylimino-tri(pyrrolidine)phosphine;
[0014] When the degradation liquid comprises a metal ion degradation liquid, the metal ion degradation liquid comprises metal ions, and the metal ions comprise one or more of zinc ions, copper ions, aluminum ions, and iron ions.
[0015] In some embodiments of the present application, when the degradation liquid includes an acidic degradation liquid, the concentration of the acidic compound in the acidic degradation liquid is 2.8-3.5 mol / L, the preset weight ratio is 1:9.2-12.4, and the preset conditions include: maintaining 1.0-3.0h at a temperature of 130-140°C and a stirring rate of 400-700r / min.
[0016] In some embodiments of the present application, when the degradation liquid includes an alkaline degradation liquid, the concentration of the alkaline compound in the alkaline degradation liquid is 3.2-4.6 mol / L, the preset weight ratio is 1:7.3-10.8, and the preset conditions include: maintaining 1.5-3.0h at a temperature of 150-180°C and a stirring rate of 0-500r / min.
[0017] In some embodiments of the present application, when the degradation liquid includes a metal ion degradation liquid, the concentration of metal ions in the metal ion degradation liquid is 2.0-5.0 mol / L, the preset weight ratio is 1:12.0-15.0, and the preset conditions include: maintaining for 3.0-5.5 hours at a temperature of 140-150°C and a stirring rate of 100-300 r / min.
[0018] In some embodiments of the present application, the thermosetting resin matrix includes one of an epoxy acrylate resin matrix, a polyurethane resin matrix, and an epoxy resin matrix.
[0019] In some embodiments of the present application, the epoxy acrylate resin matrix includes the following raw materials in parts by weight:
[0020] 40-80 parts of epoxy acrylate resin, 0-60 parts of acrylic resin or methacrylic resin, 10-50 parts of diluent monomer, 0.5-5 parts of first catalyst, 0-10 parts of anti-ultraviolet agent, 0-10 parts of antioxidant, 0.1-5 parts of inhibitor, 0.01-10 parts of photoinitiator;
[0021] The polyurethane resin matrix comprises the following raw materials in parts by weight:
[0022] 40-50 parts of polyol, 50-60 parts of isocyanate, 0.1-0.5 parts of second catalyst, 0.1-10 parts of plasticizer;
[0023] The epoxy resin matrix comprises the following raw materials in parts by weight:
[0024] 40-70 parts by weight of epoxy resin and 5.2-7.5 parts by weight of curing agent.
[0025] According to a second aspect of the present application, there is provided an application of recycled materials of a thermosetting resin-based composite material frame, comprising:
[0026] According to the above-mentioned recovery method, the degradation products after the degradation of the thermosetting resin matrix are collected;
[0027] The degradation products are used to prepare foaming materials, adhesives and coatings.
[0028] The technical solution provided by this application may have the following beneficial effects:
[0029] The present application can open the CO bond in the thermosetting resin matrix by using a degradation liquid, so as to chemically degrade the thermosetting resin matrix containing ester bonds and / or urethane bonds in the composite material frame, and obtain small molecules or low molecular polymers containing polyols, thereby achieving the degradation of the thermosetting resin after cross-linking polymerization. The resin products after degradation are mainly small molecules or oligomers of polyols, which can be further applied to the fields of polyurethane foaming, coatings, adhesives, etc.; the recycled fibers can be applied to the fields of reinforced composite materials such as resins or concrete.
[0030] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0032] Figure 1 The present invention is a flow chart of a method for recycling a thermosetting resin-based composite material frame according to an exemplary embodiment.
[0033] Figure 2a is a schematic diagram showing the degradation of a cured polyurethane resin according to an exemplary embodiment.
[0034] Figure 2b is a schematic diagram showing the degradation of a cured epoxy resin according to an exemplary embodiment.
[0035] Figure 2c is a schematic diagram showing the degradation of a cured acrylic resin according to an exemplary embodiment.
[0036] Figure 3 This is an electron microscope image of the foamed material shown in Application Example 7.
[0037] Figure 4 This is an electron microscope image of the SMC board shown in Application Example 8. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in combination with the embodiments of the present application and the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.
[0039] At present, there are three main methods for recycling composite materials: mechanical method, pyrolysis method and chemical solvent method. The mechanical method mainly processes the composite materials through cutting, crushing, grinding and other equipment to obtain mixed powder, and can also further screen and separate resin and fiber. It is mainly used in outdoor public facilities and construction fields. This recycling method is relatively simple to operate, but the added value of recycling is low, and the recycling process consumes a lot of energy and causes a lot of pollution. The pyrolysis method is to break the chemical bonds of the thermosetting resin matrix under heating conditions and decompose it into small molecular compounds to recycle the resin and fiber, but this method has high equipment requirements, high energy consumption, and serious environmental pollution. The chemical solvent method can theoretically achieve the degradation of composite materials by selectively breaking the specific chemical bonds of the resin matrix through degradation liquid, and then achieve the recovery of resin and reuse of fiber through processes such as fractionation. The materials recycled by this method have high added value, and the chemical degradation liquid can be recycled.
[0040] In the related technologies, the research on the recycling of composite materials is mostly focused on the recycling and reuse of high-cost carbon fibers, and it is necessary to select specific degradation liquids for specific resins, which increases the difficulty of recycling composite materials with different compositions. In addition, since the resin matrix in the composite frame is usually prepared with a variety of resins, the cost of the resin matrix in the raw materials is much higher than that of the fiber, and it has the characteristics of large scale and low recycling added value. Therefore, how to truly solve the low-cost and efficient degradation and recycling of the frame is a difficult problem for the development of the industry.
[0041] In order to solve the above technical problems, the present application provides a method for recycling a thermosetting resin-based composite material frame, wherein the thermosetting resin-based composite material frame includes a thermosetting resin matrix, and the recycling method includes: mixing the thermosetting resin-based composite material frame with a degradation liquid according to a preset weight ratio to obtain a mixture; reacting the mixture under preset conditions to degrade the thermosetting resin matrix; wherein the thermosetting resin matrix includes ester bonds and / or carbamate bonds; and the preset weight ratio is 1:3.0-50.0. The present application uses a degradation liquid to open the CO bonds in the thermosetting resin matrix to chemically degrade the thermosetting resin matrix containing ester bonds and / or carbamate bonds in the composite material to obtain a small molecule or low molecular weight polymer containing a polyol, thereby achieving the degradation of the thermosetting resin after cross-linking polymerization.
[0042] Some specific implementation modes described below are intended to facilitate those skilled in the art to understand the present embodiment, and the present embodiment is not limited to some specific implementation modes described below.
[0043] like Figure 1 As shown, an exemplary embodiment of the present application provides a thermosetting resin-based composite material frame, the thermosetting resin-based composite material frame includes a thermosetting resin matrix, and the recycling method includes:
[0044] S110, mixing a thermosetting resin-based composite material frame and a degradation liquid in a preset weight ratio to obtain a mixture; wherein the thermosetting resin matrix includes ester bonds and / or urethane bonds; and the preset weight ratio is 1:3.0-50.0.
[0045] In step S110, the thermosetting resin-based composite material frame includes a thermosetting resin matrix and reinforcing fibers, wherein the reinforcing fibers can significantly improve the mechanical properties and durability of the composite material frame, and the reinforcing fibers include glass fibers, carbon fibers, basalt fibers, aramid fibers, etc.; the thermosetting resin matrix can fix the reinforcing fibers in a desired shape and relative position, so that the composite material frame maintains a good overall structural stability, and the thermosetting resin matrix generally includes acrylic resin, polyurethane resin, epoxy resin, vinyl resin, etc. Such resins generally contain ester bonds or carbamate bonds, which have the characteristics of reversibility; the degradation liquid is mixed with the thermosetting resin-based composite material frame according to a preset weight ratio, so as to degrade the thermosetting resin matrix. Exemplarily, the preset weight ratio is 1:3.0, 1:10.4, 1:23.6, 1:35.0, 1:42.8, 1:50.0. The preset weight ratio may also be any ratio between the exemplary ratios, for example, the preset weight ratio may also be any ratio between 1:23.6-42.8.
[0046] S120, reacting the mixture under preset conditions to degrade the thermosetting resin matrix.
[0047] In step S120, the mixture is reacted under preset conditions to open the CO bonds in the thermosetting resin matrix, degrading it into a small molecule or low molecular weight polymer resin containing polyols, and separating it from the reinforcing fibers, so that the small molecule or low molecular weight polymer resin and the reinforcing fibers can be reused respectively.
[0048] In this embodiment, according to the characteristics of the molecular structure of the polymer resin in the resin matrix, the bond energies of the degradable ester bonds and the carbamate bonds are different. By changing the preset mass ratio and the preset conditions, the degradation reaction activity is adjusted so that the purpose of degradation can be achieved for thermosetting resin matrices of different compositions, and it has a wide range of applications.
[0049] In an exemplary embodiment, the preset conditions include: maintaining the temperature at 20-300° C., the pressure at 0-20 MPa, and the stirring rate at 0-2000 r / min for 0.5-24.0 h.
[0050] In this embodiment, the preset conditions can be adjusted according to different types of thermosetting resin matrix.
[0051] Exemplarily, in one embodiment, the preset conditions include: maintaining for 24.0 hours under the conditions of a temperature of 20° C., a pressure of 20 MPa, and a stirring rate of 2000 r / min.
[0052] In another embodiment, the preset conditions include: maintaining the temperature at 100° C. and the pressure at 10 MPa for 0.5 h.
[0053] In another embodiment, the preset conditions include: maintaining the temperature at 300° C. and the stirring rate at 1000 r / min for 12.0 h.
[0054] In an exemplary embodiment, the degradation liquid includes one of an acidic degradation liquid, an alkaline degradation liquid, and a metal ion degradation liquid.
[0055] In this embodiment, by using an acidic degradation liquid, an alkaline degradation liquid, or a metal ion degradation liquid, effective degradation of a thermosetting resin matrix containing ester bonds and / or urethane bonds can be achieved.
[0056] In an exemplary embodiment, when the degradation liquid includes an acidic degradation liquid, the acidic degradation liquid includes an acidic compound, and the acidic compound includes one or more of sulfuric acid, hydrochloric acid, nitric acid, carbonic acid, p-toluenesulfonic acid, acetic acid, phosphotungstic acid, trifluoroacetic acid, and trifluoromethanesulfonic acid.
[0057] In this embodiment, the acidic degradation liquid may further include a solvent, wherein the solvent may be, for example, water, phenylethyl alcohol, ethylene glycol, polyethylene glycol, ethanol, ethyl acetate, methyl formate, acetone, 1,4-dioxane, ethylene glycol ethyl ether acetate; depending on the composition of the acidic compound, a solvent having good compatibility with the acidic compound may be selected.
[0058] In an exemplary embodiment, when the degradation liquid includes an alkaline degradation liquid, the alkaline degradation liquid includes an alkaline compound, and the alkaline compound includes one or more of potassium hydroxide, sodium hydroxide, sodium bicarbonate, aluminum hydroxide, sodium carbonate, 4-dimethylaminopyridine, alkyl copper lithium, and tert-butylimino-tri(pyrrolidine)phosphine (tBu-P1).
[0059] In this embodiment, the alkaline degradation liquid may further include a solvent, wherein the solvent may be water, phenylethyl alcohol, ethylene glycol, polyethylene glycol, ethanol, ethyl acetate, methyl formate, acetone, 1,4-dioxane, ethylene glycol ethyl ether acetate; depending on the composition of the alkaline compound, a solvent having good compatibility with the alkaline compound may be selected.
[0060] In an exemplary embodiment, when the degradation solution includes a metal ion degradation solution, the metal ion degradation solution includes metal ions, and the metal ions include one or more of zinc ions, copper ions, aluminum ions, and iron ions.
[0061] In this embodiment, the metal ion degradation liquid may further include a solvent, wherein the solvent may be water, phenylethyl alcohol, ethylene glycol, polyethylene glycol, ethanol, ethyl acetate, methyl formate, acetone, 1,4-dioxane, ethylene glycol ethyl ether acetate; depending on the composition of the metal ions, a solvent having good compatibility with the metal ions may be selected.
[0062] In an exemplary embodiment, when the degradation liquid includes an acidic degradation liquid, the concentration of the acidic compound in the acidic degradation liquid is 2.8-3.5 mol / L, the preset weight ratio is 1:9.2-12.4, and the preset conditions include: maintaining 1.0-3.0h at a temperature of 130-140°C and a stirring rate of 400-700r / min.
[0063] Exemplarily, in one embodiment, the concentration of the acidic compound in the acidic degradation liquid is 2.8 mol / L, the preset weight ratio is 1:9.2, and the preset conditions include: maintaining for 3.0 hours at a temperature of 140° C. and a stirring rate of 700 r / min.
[0064] In another embodiment, the concentration of the acidic compound in the acidic degradation liquid is 2.8-3.5 mol / L, the preset weight ratio is 1:10.8, and the preset conditions include: maintaining for 2.0 h at a temperature of 135° C. and a stirring rate of 600 r / min.
[0065] In another embodiment, the concentration of the acidic compound in the acidic degradation liquid is 3.5 mol / L, the preset weight ratio is 1:12.4, and the preset conditions include: maintaining 1.0 h at a temperature of 130° C. and a stirring rate of 400 r / min.
[0066] In an exemplary embodiment, the thermosetting resin matrix includes one of an epoxy acrylate resin matrix, a polyurethane resin matrix, and an epoxy resin matrix.
[0067] In this embodiment, the concentration of the acidic degradation liquid, the preset weight ratio and the preset conditions can be adjusted according to the composition of the thermosetting resin matrix, so that the degradation rate of the thermosetting resin matrix can reach more than 95%, thereby achieving effective degradation of the thermosetting resin matrix.
[0068] in, Figure 2a-2c The degradation principle of thermosetting resin matrix is shown, such as Figure 2a As shown in FIG. 1 , the cured polyurethane resin can generate primary amines and polyols after being degraded by the degradation liquid; as shown in FIG. Figure 2b As shown in FIG. 1 , the cured epoxy resin can generate polyols and dibasic acids after being degraded by the degradation liquid; Figure 2c As shown, the cured acrylic resin can generate polyacid oligomers and polyols after being degraded by the degradation liquid.
[0069] In the following exemplary acidic degradation liquid, the acidic compound is toluenesulfonic acid, the solvent is ethylene glycol, and the concentration of the acidic compound is 2.8-3.1 mol / L.
[0070] When the thermosetting resin matrix is an epoxy acrylate resin matrix, the preset weight ratio is 1:9.6-10.4, and the preset conditions include: maintaining 1.5-2.5 hours at a temperature of 136-140°C and a stirring rate of 450-550 r / min. In this way, the degradation rate of the thermosetting resin matrix can reach more than 97.10%.
[0071] When the thermosetting resin matrix is a polyurethane resin matrix, the preset weight ratio is 1:9.6-10.4, and the preset conditions include: maintaining 1.0-1.4 hours at a temperature of 130-135°C and a stirring rate of 450-550 r / min. In this way, the degradation rate of the thermosetting resin matrix can reach more than 95.46%.
[0072] In an exemplary embodiment, when the degradation liquid includes an alkaline degradation liquid, the concentration of the alkaline compound in the alkaline degradation liquid is 3.2-4.6 mol / L, the preset weight ratio is 1:7.3-10.8, and the preset conditions include: maintaining 1.5-3.0h at a temperature of 150-180°C and a stirring rate of 0-500r / min.
[0073] Exemplarily, in one embodiment, the concentration of the alkaline compound in the alkaline degradation solution is 3.2 mol / L, the preset weight ratio is 1:7.3, and the preset conditions include: maintaining for 3.0 h at a temperature of 180° C. and a stirring rate of 500 r / min.
[0074] In another embodiment, the concentration of the alkaline compound in the alkaline degradation solution is 3.8 mol / L, the preset weight ratio is 1:9.5, and the preset conditions include: maintaining for 2.4 hours at a temperature of 160° C. and a stirring rate of 200 r / min.
[0075] In another embodiment, the concentration of the alkaline compound in the alkaline degradation solution is 4.6 mol / L, the preset weight ratio is 1:10.8, and the preset conditions include: maintaining the temperature at 150° C. for 1.5 hours.
[0076] In the following exemplary alkaline degradation solution, the alkaline compound is alkyl copper lithium, the solvent is polyethylene glycol, and the concentration of the alkaline compound is 3.8-4.2 mol / L.
[0077] When the thermosetting resin matrix is an epoxy acrylate resin matrix, the preset weight ratio is 1:7.8-8.4, and the preset conditions include: standing for 1.8-2.2 hours at a temperature of 170-180° C. In this way, the degradation rate of the thermosetting resin matrix can reach more than 98.03%.
[0078] When the thermosetting resin matrix is a polyurethane resin matrix, the preset weight ratio is 1:7.8-8.4, and the preset conditions include: standing for 1.8-2.2 hours at a temperature of 150-160° C. In this way, the degradation rate of the thermosetting resin matrix can reach more than 97.53%.
[0079] When the thermosetting resin matrix is an epoxy resin matrix, the preset weight ratio is 1:9.8-10.8, and the preset conditions include: standing for 1.8-2.2 hours at a temperature of 170-180° C. In this way, the degradation rate of the thermosetting resin matrix can reach more than 94.02%.
[0080] In an exemplary embodiment, when the degradation liquid includes a metal ion degradation liquid, the concentration of metal ions in the metal ion degradation liquid is 2.0-5.0 mol / L, the preset weight ratio is 1:12.0-15.0, and the preset conditions include: maintaining 3.0-5.5h at a temperature of 140-150°C and a stirring rate of 100-300r / min.
[0081] Exemplarily, in one embodiment, the concentration of metal ions in the metal ion degradation solution is 2.0-5.0 mol / L, the preset weight ratio is 1:12.0, and the preset conditions include: maintaining for 5.5 hours at a temperature of 150° C. and a stirring rate of 300 r / min.
[0082] In another embodiment, the concentration of metal ions in the metal ion degradation solution is 2.0-5.0 mol / L, the preset weight ratio is 1:13.5, and the preset conditions include: maintaining for 4.5 hours at a temperature of 145° C. and a stirring rate of 200 r / min.
[0083] In another embodiment, the concentration of metal ions in the metal ion degradation solution is 2.0-5.0 mol / L, the preset weight ratio is 1:15.0, and the preset conditions include: maintaining for 3.0 hours at a temperature of 150° C. and a stirring rate of 100 r / min.
[0084] In the following exemplary metal ion degradation solution, the metal ion compound is zinc chloride, the solvent is ethyl acetate, and the concentration of the metal ion is 2.0-5.0 mol / L.
[0085] When the thermosetting resin matrix is an epoxy acrylate resin matrix, the preset weight ratio is 1:14.0-15.0, and the preset conditions include: maintaining 5.0-5.5 hours at a temperature of 145-150°C and a stirring rate of 100-200 r / min. In this way, the degradation rate of the thermosetting resin matrix can reach more than 95.21%.
[0086] When the thermosetting resin matrix is a polyurethane resin matrix, the preset weight ratio is 1:12.0-13.5, and the preset conditions include: maintaining 3.0-4.0 hours at a temperature of 140-144°C and a stirring rate of 210-300 r / min. In this way, the degradation rate of the thermosetting resin matrix can reach more than 98.74%.
[0087] In an exemplary embodiment, the epoxy acrylate resin matrix includes the following raw materials in parts by weight: 40-80 parts of epoxy acrylate resin, 0-60 parts of acrylic resin or methacrylic resin, 10-50 parts of diluent monomer, 0.5-5 parts of first catalyst, 0-10 parts of anti-ultraviolet agent, 0-10 parts of antioxidant, 0.1-5 parts of inhibitor, and 0.01-10 parts of photoinitiator.
[0088] In this embodiment, epoxy acrylate resin is a kind of weather-resistant resin containing ester bonds, and the main resin component contains one or more epoxy acrylate resins, and the epoxy acrylate resin includes one or more of bisphenol A epoxy acrylate resin, novolac epoxy acrylate resin, and modified epoxy acrylate resin, wherein the weight ratio of bisphenol A epoxy acrylate resin, novolac epoxy acrylate resin, and multifunctional polyester modified epoxy acrylate resin can be, for example, 1.2-1.4:0.8-1.1:1. The diluent monomer includes one or more of methyl methacrylate (MMA), isobornyl acrylate (IBOA), β-hydroxyethyl methacrylate (HEMA), β-carboxyethyl acrylate (β-CEA), and hexanediol diacrylate (HDDA). The first catalyst includes one or more of benzophenone catalysts, heterocyclic aromatic ketone catalysts, iron aromatic salt catalysts, and alkyl sulfonium salt catalysts. The anti-ultraviolet agent includes one or more of UV-1180, titanium dioxide, and zinc oxide. The antioxidant includes one or more of antioxidant 1010, antioxidant 1076, and composite phosphite antioxidant. The inhibitor includes one or more of hydroquinone and p-tert-butylcatechol. The photoinitiator includes one or more of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO) and photoinitiator 819. The main molecular chain and side chain of the epoxy acrylate resin in this embodiment contain catalytically degradable ester bonds, and the CO bond can be opened by a degradation liquid to obtain a polyol compound of a small molecule or low molecular weight polymer.
[0089] Illustratively, in one embodiment, the epoxy acrylate resin matrix includes the following raw materials in parts by weight: 40 parts of epoxy acrylate resin, 10 parts of diluent monomer, 0.5 parts of first catalyst, 0.1 parts of inhibitor, and 0.01 parts of photoinitiator.
[0090] In another embodiment, the epoxy acrylate resin matrix includes the following raw materials in parts by weight: 60 parts of epoxy acrylate resin, 30 parts of acrylic resin, 30 parts of diluent monomer, 2 parts of first catalyst, 5 parts of anti-ultraviolet agent, 3 parts of antioxidant, 2.5 parts of inhibitor, and 5.6 parts of photoinitiator.
[0091] In another embodiment, the epoxy acrylate resin matrix includes the following raw materials in parts by weight: 80 parts of epoxy acrylate resin, 60 parts of methacrylic resin, 50 parts of diluent monomer, 5 parts of first catalyst, 10 parts of anti-ultraviolet agent, 10 parts of antioxidant, 5 parts of inhibitor, and 10 parts of photoinitiator.
[0092] In an exemplary embodiment, the polyurethane resin matrix includes the following raw materials in parts by weight: 40-50 parts of polyol, 50-60 parts of isocyanate, 0.1-0.5 parts of a second catalyst, and 0.1-10 parts of a plasticizer.
[0093] In the present embodiment, the polyurethane resin is a resin containing multiple carbamate bonds on a molecular chain, and the polyol component includes one or more of polyester polyols and polyether polyols. For example, the polyol includes polyoxypropylene triol and polyoxypropylene ether diol in a weight ratio of 1.5-2.8:1. Isocyanates include one or more of aromatic isocyanates and derivatives thereof, aliphatic isocyanates and derivatives thereof. For example, isocyanates include diphenylmethane diisocyanate and isophorone diisocyanate in a weight ratio of 1:1.3-2.5. The second catalyst includes one or more of a tertiary amine catalyst and an organic metal catalyst. The plasticizer includes epoxidized soybean oil. Since the molecular chain of this type of polyurethane resin contains carbamate bonds, the CO bonds are opened under the catalytic action of the degradation liquid to obtain polyol compounds of small molecules or low molecular weight polymers.
[0094] Illustratively, in one embodiment, the polyurethane resin matrix includes the following raw materials in parts by weight: 40 parts of polyol, 50 parts of isocyanate, 0.1 parts of the second catalyst, and 0.1 parts of a plasticizer.
[0095] In another embodiment, the polyurethane resin matrix includes the following raw materials in parts by weight: 45 parts of polyol, 55 parts of isocyanate, 0.3 parts of the second catalyst, and 5 parts of plasticizer.
[0096] In another embodiment, the polyurethane resin matrix includes the following raw materials in parts by weight: 50 parts of polyol, 60 parts of isocyanate, 0.5 parts of the second catalyst, and 10 parts of a plasticizer.
[0097] In an exemplary embodiment, the epoxy resin matrix includes the following raw materials in parts by weight: 40-70 parts by weight of epoxy resin, 30-50 parts by weight of curing agent, and 0-10 parts by weight of additive.
[0098] In this embodiment, the epoxy resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin. For example, the epoxy resin includes bisphenol A epoxy resin (E-51) and novolac epoxy resin (F-44) in a weight ratio of 1.3-2.5:1. The curing agent includes methyl hexahydrophthalic anhydride (MHHPA). The additive may be, for example, a diluent, a accelerator, and the like.
[0099] Illustratively, in one embodiment, the epoxy resin matrix includes the following raw materials in parts by weight: 40 parts by weight of epoxy resin, 50 parts by weight of curing agent, and 10 parts by weight of additive.
[0100] In another embodiment, the epoxy resin matrix includes the following raw materials in parts by weight: 50 parts by weight of epoxy resin, 45 parts by weight of curing agent, and 5 parts by weight of additive.
[0101] In another embodiment, the epoxy resin matrix includes the following raw materials in parts by weight: 70 parts by weight of epoxy resin and 30 parts by weight of curing agent.
[0102] An exemplary embodiment of the present application provides an application of recycled materials of a thermosetting resin-based composite material frame, including:
[0103] According to the above recovery method, the degradation products after the degradation of the thermosetting resin matrix are collected;
[0104] The degradation products are used to prepare foaming materials, adhesives and coatings.
[0105] In this embodiment, the degradation liquid and the degradation products can be separated by fractional cooling, wherein the degradation products are small molecules of polyols or a resin mixture of oligomers. The degradation liquid can be theoretically recycled indefinitely, with a single loss rate of 0.1%-10%.
[0106] The small molecules and oligomer mixed resins in the degradation products contain a large number of hydroxyl groups. This polyhydroxyl mixture can be used as the polyol component of polyurethane foam materials. The proportion of recycled resin in the white material of polyurethane foam is 10wt%-60wt%. The prepared rigid foam material has a density, mechanical properties and pore structure at a comparable level compared to completely non-recycled materials.
[0107] The small molecule and oligomer mixed resin in the degradation product can also be used in the field of adhesives and coatings. For the epoxy acrylate resin, it has excellent corrosion resistance and can be used in anti-corrosion fields such as walls and steel structures. The amount of the recycled oligomer component added is 20wt%-50wt%, and the mechanical properties, UV resistance, chemical resistance, and moisture and heat resistance of the epoxy acrylate resin prepared by recycling are reduced by 0-10%, and it can be repeatedly used in various fields.
[0108] In addition, after the reinforcing fibers in the composite frame are separated from the thermosetting resin matrix, the recycled fibers are obtained through filtering, alcohol washing, drying and other processes, and can be broken to prepare short fibers (less than 5mm). The prepared short fibers are reinforced with resin-based or concrete-based composite materials, which can be used in the fields of construction, outdoor public facilities, etc. The recycled fibers can also be cut into long fibers (5-20mm) and used in parts in the fields of automobiles, ships, etc. through molding processes.
[0109] In order to more clearly explain the technical solution of the present application, the present application lists specific embodiments of the method for recycling thermosetting resin-based composite materials, and the beneficial effects of selecting the above-mentioned ranges of each process parameter will be explained by giving specific experimental data through specific embodiments.
[0110] Preparation Example
[0111] Preparation Example 1: A method for preparing an epoxy acrylate resin-based composite material frame, comprising the following steps:
[0112] (1) Bisphenol A epoxy acrylate resin, novolac epoxy acrylate resin and multifunctional polyester modified epoxy acrylate resin are mixed in a weight ratio of 4:3:3 to obtain a mixed resin.
[0113] (2) 50 kg of mixed resin, 15 kg of isobornyl acrylate (IBOA) and 0.75 kg of photoinitiator 819 were mixed to obtain an epoxy acrylate resin matrix.
[0114] (3) Using a pultrusion process, the glass fiber is impregnated with an epoxy acrylate resin matrix, and cured under ultraviolet light curing conditions of 315-400 nm to prepare an epoxy acrylate-based composite material frame.
[0115] Preparation Example 2: A method for preparing a polyurethane resin-based composite material frame, comprising the following steps:
[0116] (1) Diphenylmethane diisocyanate and isophorone diisocyanate are mixed in a weight ratio of 1:1.3 to obtain isocyanate; polyoxypropylene triol and polyoxypropylene ether diol are mixed in a weight ratio of 1.5:1 to obtain a polyol.
[0117] (2) 50 kg of isocyanate was used as black material, 44.7 kg of polyol, 0.3 kg of dibutyltin dilaurate and 5 kg of epoxy soybean oil were used as white material; the black material and the white material were injected into a mold, the mold temperature was controlled to be 110 ° C, glass fiber was used as reinforcing fiber, and a polyurethane resin-based composite material frame was prepared by a pultrusion process.
[0118] Preparation Example 3: A method for preparing an epoxy resin-based composite material frame, comprising the following steps:
[0119] (1) Bisphenol A epoxy resin (E-51) and novolac epoxy resin (F-44) were mixed in a weight ratio of 2:1 to obtain epoxy resin.
[0120] (2) 45 kg of epoxy resin, 45 kg of methylhexahydrophthalic anhydride, and 10 kg of other additives are mixed to obtain an epoxy resin matrix.
[0121] (3) The epoxy resin matrix is injected into the mold, the mold temperature is controlled to be 150°C, and glass fiber is used as the reinforcing fiber to prepare the epoxy resin-based composite material frame through a pultrusion process.
[0122] Example
[0123] Unless otherwise specified, the raw materials in the following examples can be obtained from commercial sources. Among them, the epoxy acrylate resin-based composite material frame is prepared by the method of Preparation Example 1; the polyurethane resin-based composite material frame is prepared by the method of Preparation Example 2; and the epoxy resin-based composite material frame is prepared by the method of Preparation Example 3.
[0124] Embodiment 1: A method for recycling a thermosetting resin-based composite material frame, comprising the following steps:
[0125] (1) Toluenesulfonic acid and ethylene glycol are mixed to obtain an acidic degradation solution having a toluenesulfonic acid concentration of 3.0 mol / L.
[0126] (2) The epoxy acrylate resin-based composite material frame and the acidic degradation liquid were mixed in a weight ratio of 1:10.0 and placed in a reactor. The reaction was maintained for 3.0 hours at a temperature of 140°C and a stirring rate of 500 r / min to degrade the epoxy acrylate resin matrix. The degradation products after degradation were separated from the glass fiber, and the degradation rate of the resin matrix was measured to be 97.52%.
[0127] Embodiment 2: A method for recycling a thermosetting resin matrix composite material frame, comprising the following steps:
[0128] (1) Alkyl copper lithium and polyethylene glycol are mixed to prepare an alkaline degradation solution with an alkyl copper lithium concentration of 4.0 mol / L.
[0129] (2) The epoxy acrylate resin-based composite material frame and the alkaline degradation liquid were mixed in a weight ratio of 1:4.0 and placed in a reactor. The mixture was kept at 180°C for 2.0 hours to degrade the epoxy acrylate resin matrix. The degradation products after degradation were separated from the glass fiber, and the degradation rate of the resin matrix was measured to be 98.03%.
[0130] Embodiment 3: A method for recycling a thermosetting resin matrix composite material frame, comprising the following steps:
[0131] (1) Zinc oxide and ethyl acetate are mixed to prepare a metal ion degradation solution having a zinc chloride concentration of 4 mol / L.
[0132] (2) The epoxy acrylate resin-based composite material frame and the alkaline degradation liquid were mixed in a weight ratio of 1:15.0 and placed in a reactor. The mixture was kept at a temperature of 150°C and a stirring rate of 200 r / min for 5.5 hours to degrade the epoxy acrylate resin matrix. The degradation products after degradation were separated from the glass fiber, and the degradation rate of the resin matrix was measured to be 96.36%.
[0133] In order to more clearly explain the technical solution of the present application, the present application also lists Examples 4-21 of the recycling method of thermosetting resin-based composite materials, wherein the formula and process of Examples 4-21 are shown in Table 1.
[0134] Table 1 shows a specific embodiment of the method for recycling the thermosetting resin-based composite material frame in the present application. It should be noted that, except for the parameters listed in Table 1, other parameters of Examples 4-21 and Example 1 are substantially the same.
[0135] Wherein, the ratio C1 is the weight ratio of the composite material frame to the degradation liquid.
[0136] Table 1 Parameter setting table of the embodiment
[0137]
[0138] Table 1 (Continued) Parameter setting table of the embodiment
[0139]
[0140] Table 1 (Continued) Parameter setting table of the embodiment
[0141]
[0142] It can be seen from Table 1 that when the method of the present application is used to recycle the thermosetting resin-based composite material frame, the degradation rate of the thermosetting resin matrix can reach more than 94%, indicating that the method of the present application can effectively realize the recycling of the cured thermosetting resin-based composite material frame.
[0143] Application Examples
[0144] The degradation products recovered in Example 1-3 contained a large amount of polyester polyols, and the degradation products were used to prepare polyurethane foam materials according to the following method.
[0145] Application Example 1: The degradation product is mixed with polyoxypropylene triol in a weight ratio of 3:7 to serve as a polyol. 35 kg of polyol is mixed with 5 kg of cyclopentane foaming agent to serve as a white material. 60 kg of polymethylene polyphenyl polyisocyanate (PAPI) is used as a black material. After the black material and the white material are evenly mixed, they are kept at a temperature of 50°C for 30 minutes to form a rigid foam by foaming and curing; then the temperature is lowered to 25°C and aged for 24 hours to obtain a foaming material.
[0146] Application Example 2: This application example differs from Application Example 1 in that the degradation products are recovered by the method of Example 2.
[0147] Application Example 3: This application example differs from Application Example 1 in that the degradation products are recovered by the method of Example 3.
[0148] Comparative Example 1: The main difference between this comparative example and Application Example 1 is that no degradation product is used in the polyol, that is, the polyol is only polyoxypropylene triol.
[0149] The properties of the foamed materials prepared in Examples 1-3 and Comparative Example 1 were tested respectively, and the test results are recorded in Table 2.
[0150] Table 2 Performance test table of foaming materials
[0151]
[0152] It can be seen from Table 2 that when the degradation product obtained by the recycling method of the present application is used to prepare the foaming material, the density, mechanical properties and pore structure of the foaming material are at a comparable level compared to the foaming material prepared using the unrecycled material.
[0153] After the epoxy acrylate-based composite material frames of Examples 1-3 are recycled and degraded, the degradation products contain a large amount of polyester polyol and acrylate, which can be used to prepare coatings according to the following method.
[0154] Application Example 4: The degradation product and bisphenol A epoxy acrylate resin are mixed in a weight ratio of 3:7 to obtain a mixed resin. 50 kg of the mixed resin, 15 kg of β-carboxyethyl acrylate (β-CEA) and 0.75 kg of initiator methyl ethyl peroxide are mixed to obtain a coating.
[0155] Application Example 5: This application example differs from Application Example 4 in that the degradation product is recovered by the method of Example 2.
[0156] Application Example 6: This application example differs from Application Example 5 in that the degradation products are recovered by the method of Example 3.
[0157] Control Example 2: The main difference between this control example and Application Example 4 is that no degradation product is used in the raw materials, that is, the mixed resin is replaced by an equal amount of bisphenol A epoxy acrylate resin.
[0158] The properties of the coatings prepared in Examples 4-6 and Comparative Example 2 were tested respectively, and the test results are recorded in Table 3.
[0159] Table 3 Performance test table of coatings
[0160] performance Application Example 4 Application Example 5 Application Example 6 Comparative Example 2 Solid content (%) 58 60 58 56 Viscosity(cps) 549 558 530 410 Gel time (min) 34 32 37 28 Tensile strength(MPa) 72 79 65 82 Tensile modulus(GPa) 3.05 2.96 2.87 3.12 Elongation at break (%) 5.1 4.7 5.5 5.2 Heat deformation temperature(℃) 93 85 82 102 Hardness(Barcol) 29 31 27 34
[0161] It can be seen from Table 3 that when the coating is prepared using the degradation product obtained by the recycling method of the present application, the mechanical properties and heat deformation temperature of the coating are at a comparable level compared to the coating prepared using unrecycled materials.
[0162] After the polyurethane-based composite material frame of Example 4 is recycled and degraded, the degradation product contains a certain amount of polyoxypropylene triol, polyether diol and oligomer polyol compounds. The degradation product is used to prepare a polyurethane foam material according to the following method.
[0163] Application Example 7: Mix the degradation product with polyoxypropylene triol in a weight ratio of 5:5 to form a polyol. Mix 35kg of polyol with 5kg of cyclopentane foaming agent to form a white material. Use 60kg of polymethylene polyphenyl polyisocyanate (PAPI) as a black material. After the black material and the white material are evenly mixed, keep them at a temperature of 50°C for 20 minutes to foam and solidify to form a hard foam; then cool to 25°C and mature for 24 hours to obtain a foaming material. Among them, the microscopic pore structure of the foaming material is as follows: Figure 3 As shown, from Figure 3 It can be seen that when the degradation product obtained by the recovery method of the present application is used to prepare the foaming material, a better pore structure can be obtained.
[0164] The performance of the foamed material prepared in Example 7 was tested, and the test results are recorded in Table 4.
[0165] Table 4 Performance test table of foaming materials
[0166]
[0167] It can be seen from Table 4 that when the degradation product obtained by the recycling method of the present application is used to prepare the foaming material, the density, mechanical properties and pore structure of the foaming material are at a comparable level compared to the foaming material prepared using the unrecycled material.
[0168] After the thermosetting resin-based composite material frame is degraded by the method of the present application, the reinforcing fibers can be separated from the degradation products by processes such as fractionation to obtain recycled reinforcing fibers, which is described below using the recycled glass fibers in Example 1 as an example.
[0169] Application Example 8: Cut the recycled glass fiber to obtain glass fiber with a length of 10-30 mm. Make the glass fiber and epoxy resin into sheet molding compound (SMC), and further make the SMC material into composite material board through molding process. Figure 4 As shown, the SMC board prepared by the glass fiber recycled by the method of the present application can meet the required microstructure requirements and no obvious defects are found. The SMC material made of such recycled reinforcing fiber and resin can be further used in the fields of new energy vehicle battery box upper cover, engine cover, trunk cover, etc.
[0170] In summary, the method of the present application can be used to chemically degrade the thermosetting resin matrix containing ester bonds and / or carbamate bonds in the composite material frame, and the degraded resin product can be further used in the fields of polyurethane foaming, coatings, adhesives, etc.; the recycled fibers can be used in the field of reinforced composite materials such as resins or concrete.
[0171] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0172] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for recycling a thermosetting resin-based composite material frame, characterized in that: The thermosetting resin-based composite material includes a thermosetting resin matrix, and the recycling method includes: Mixing the thermosetting resin-based composite material frame and the degradation liquid according to a preset weight ratio to obtain a mixture; allowing the mixture to react under preset conditions to degrade the thermosetting resin matrix; Wherein, the thermosetting resin matrix includes ester bonds and / or urethane bonds; The preset weight ratio is 1:3.0-50.
0.
2. The method for recycling a thermosetting resin-based composite material frame according to claim 1, characterized in that: The preset conditions include: maintaining the temperature at 20-300° C., the pressure at 0-20 MPa, and the stirring rate at 0-2000 r / min for 0.5-24.0 h.
3. The method for recycling a thermosetting resin-based composite material frame according to claim 1, characterized in that: The degradation liquid includes one of an acidic degradation liquid, an alkaline degradation liquid and a metal ion degradation liquid.
4. The method for recycling a thermosetting resin-based composite material frame according to claim 3, characterized in that: When the degradation liquid comprises an acidic degradation liquid, the acidic degradation liquid comprises an acidic compound, and the acidic compound comprises one or more of sulfuric acid, hydrochloric acid, nitric acid, carbonic acid, p-toluenesulfonic acid, acetic acid, phosphotungstic acid, trifluoroacetic acid, and trifluoromethanesulfonic acid; When the degradation liquid comprises an alkaline degradation liquid, the alkaline degradation liquid comprises an alkaline compound, and the alkaline compound comprises one or more of potassium hydroxide, sodium hydroxide, sodium bicarbonate, aluminum hydroxide, sodium carbonate, 4-dimethylaminopyridine, alkyl copper lithium, and tert-butylimino-tri(pyrrolidine)phosphine; When the degradation liquid comprises a metal ion degradation liquid, the metal ion degradation liquid comprises metal ions, and the metal ions comprise one or more of zinc ions, copper ions, aluminum ions, and iron ions.
5. The method for recycling a thermosetting resin-based composite material frame according to claim 4, characterized in that: When the degradation liquid includes an acidic degradation liquid, the concentration of the acidic compound in the acidic degradation liquid is 2.8-3.5 mol / L, the preset weight ratio is 1:9.2-12.4, and the preset conditions include: maintaining 1.0-3.0h at a temperature of 130-140°C and a stirring rate of 400-700r / min.
6. The method for recycling a thermosetting resin-based composite material frame according to claim 4, characterized in that: When the degradation liquid includes alkaline degradation liquid, the concentration of alkaline compounds in the alkaline degradation liquid is 3.2-4.6 mol / L, the preset weight ratio is 1:7.3-10.8, and the preset conditions include: maintaining 1.5-3.0h at a temperature of 150-180°C and a stirring rate of 0-500r / min.
7. The method for recycling a thermosetting resin-based composite material frame according to claim 4, characterized in that: When the degradation liquid includes a metal ion degradation liquid, the concentration of metal ions in the metal ion degradation liquid is 2.0-5.0 mol / L, the preset weight ratio is 1:12.0-15.0, and the preset conditions include: maintaining 3.0-5.5h at a temperature of 140-150°C and a stirring rate of 100-300r / min.
8. The method for recycling a thermosetting resin-based composite material frame according to claim 1, characterized in that: The thermosetting resin matrix includes one of an epoxy acrylate resin matrix, a polyurethane resin matrix, and an epoxy resin matrix.
9. The method for recycling a thermosetting resin-based composite material frame according to claim 8, characterized in that: The epoxy acrylate resin matrix comprises the following raw materials in parts by weight: 40-80 parts of epoxy acrylate resin, 0-60 parts of acrylic resin or methacrylic resin, 10-50 parts of diluent monomer, 0.5-5 parts of first catalyst, 0-10 parts of anti-ultraviolet agent, 0-10 parts of antioxidant, 0.1-5 parts of inhibitor, 0.01-10 parts of photoinitiator; The polyurethane resin matrix comprises the following raw materials in parts by weight: 40-50 parts of polyol, 50-60 parts of isocyanate, 0.1-0.5 parts of second catalyst, 0.1-10 parts of plasticizer; The epoxy resin matrix comprises the following raw materials in parts by weight: 40-70 parts by weight of epoxy resin, 30-50 parts by weight of curing agent, and 0-10 parts by weight of additive.
10. An application of recycled materials for thermosetting resin-based composite material frames, characterized in that: include: According to any one of claims 1 to 9, collecting degradation products of the thermosetting resin matrix after degradation; The degradation products are used to prepare foaming materials, adhesives and coatings.